(untitled) (Research, Society and Development, 2021)
This article aims to reflect on the health-disease process in old age, from the perspective of normal and pathological. It is a theoretical-reflective essay, with a philosophical basis, which took place through the work “O normal e o patológico”, by the French philosopher and physician Georges Canguilhem. To support the reflection and discussion, scientific publications were used on the themes of human aging, old age, health-disease process in aging and old age, normal and pathological, and some public policies. The reflection proposes two chapters: “the health-disease process in old age: what is normal and what is pathological?” and “aging and old age in terms of public health policies”. The paradigm shift regarding aging and old age is still incipient, both in society and in public health policies. Aging is complex, and there is no need to set limits or boundaries between these two aspects, or between health and disease.